METHODICAL ASPECTS OF STUDYING THE FUNDAMENTALS OF ALGORITHMIZATION AND PROGRAMMING LANGUAGE PYTHON SCHOOL COURSE IN INFORMATICS IN HIGH SCHOOL - Kobynyk, Taras; Kohut, Uliana; Zhydyk, Volodymyr (Physical and Mathematical Education, 2021)
The article investigates the problems of studying the elements of programming in the school course of computer science.Formulation of the problem. An important pedagogical problem is the formation and development of the algorithmic skills of students, the improvement of their professional training. The problems of improving the methodological system of teaching computer science in general secondary school require further research in order to find more effective forms, methods and means of teaching. It is necessary to ensure the formation in students of the competencies necessary for a conscious choice of the future profile of education. Students should understand the relationship between theoretical and applied informatics, know how to use various types of information technology in professional activities. And also the advantages of the Python language in teaching informatics and the features of their pedagogical use in teaching the basics of algorithms are determined.Materials and methods. To achieve this goal, a set of methods was used: a systematic analysis of scientific works covering the problem of research, studying the domestic experience of studying programming elements in a school computer science course; generalization and substantiation of the theoretical foundations of using the PYTHON programming language in the school computer science course.Results. The main characteristics of the Python programming language are considered and the possibilities of using this language in the process of teaching the basics of algorithmization in the school computer science course are presented. The study of the basics of algorithms and programming is one of the means of forming the operational style of thinking. Knowledge of this section presupposes the ability to formalize the task, determine the connections between the parts in it, choose the most effective algorithm for solving the problem, and the ability to correctly interpret and analyze the results obtained.Conclusions. The Python language is one of the most popular programming languages. It finds its application in various fields. According to the labor market, there is a need for specialists who could create software products in the Python language. The institutions of general secondary education did not remain aloof from this process. School textbook authors are starting to incorporate Python into their content. Thus, there is a need for the development of teaching materials for the study of the elements of algorithmization and programming in Python. The methodological significance of this section of the school computer science course lies in the disclosure of the importance of algorithms. Fundamentals of Algorithmization and Programming is one of the main content lines of the computer science course in basic school.
Keywords: institution of general secondary education; school course in computer science; the basics of algorithms; programming; programming language Python